Green Accounting and Corporate Disclosure: Enhancing ESG Transparency in the Digital Age - Erniyati Caronge; Rahma Nurzianti; Rachel Chan; Izzul Ashlah; Ryan Teo (Journal Markcount Finance, 2025)
The increasing importance of environmental, social, and governance (ESG) factors has driven corporations to adopt green accounting practices and enhance corporate disclosure, particularly in the digital age where transparency is critical for stakeholder trust. Traditional financial reporting often overlooks environmental and social impacts, limiting investors' ability to assess sustainability performance. Green accounting integrates environmental costs and benefits into financial statements, while digital platforms facilitate real-time disclosure and broader stakeholder engagement. This study investigates the role of green accounting and digital corporate disclosure in enhancing ESG transparency. A mixed-methods research design was employed, combining quantitative analysis of corporate ESG reports from 120 publicly listed firms with qualitative interviews of accounting and sustainability professionals. Data were analyzed to evaluate disclosure quality, stakeholder accessibility, and alignment with ESG reporting standards. Findings indicate that firms implementing green accounting and leveraging digital disclosure tools demonstrate higher ESG transparency, improved stakeholder trust, and more informed investment decisions. Challenges include standardization of reporting metrics, data reliability, and integration of digital reporting systems. The study concludes that the integration of green accounting with digital disclosure mechanisms is essential for promoting ESG accountability and sustainability performance. Policymakers and corporate leaders should prioritize standardized frameworks and digital tools to ensure consistent, accurate, and transparent ESG reporting in the evolving business landscape.